ASSESSMENT OF SECURITY MEASURES IN UNIVERSITIES FOR ENFORCEMENT OF INTEGRITY OF INFORMATION SYSTEMS IN KISUMU AND SIAYA COUNTIES, KENYA - Musyoka, Martin M. N.; Raburu, George; Yoga, Castro; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
An ICT policy safeguards Integrity of Information Systems and ensures business continuity. Thisstudy sought to assess the level of compliance by Universities to their ICT security policies byassessing the integrity pillar. Literature review on Integrity of Information Systems as well asinternational standards and regulations such as HIPAA, FERPA, SOX and ISO 270003 thattouch on CIA was carried out. A cross-sectional survey study design incorporated selfadministeredquantitative and qualitative research that was carried out in eight campuses withinKisumu and Siaya Counties. The survey was conducted on universities that gave authorization ofthe survey to go on. Stratified sampling method was used to arrive at the right population ofrespondents in the universities. The study targeted ten campuses within the two counties but onlyeight authorized the study. The findings of this study reveals that overall compliance ratings inthe three key pillars of IT security were below 50% on compliance ratings with integrity at 30%This study contributes to policy, practice and theory at county and individual level in two ways.Firstly it came up with empirical data on state of compliance to ICT policies in universities andsecondly it will provide the government and the institutions’ management with an objectiveprofile of issues and a proactive approach that can solve the issues in cost effective manner.